La otra dimensión del derecho - Legendre, Pierre (2016)
In times at which economic logic and a one-dimensional discourse of science silence alternative ways of thinking in our societies, this paper invites us to understand the law from a largely unexplored dimension: the dimension that institutes life, binding the social, the biological and the unconscious in a space that reproduces the logic of Interdiction. To achieve this goal, this paper begins by exploring the obstacles that make jurists unable to conceive a link between their discipline and psychoanalysis, as well as incapable of opening the law to its analysis. Among these, we encounter conceiving the legal system as the discourse of Reason in the West, construction which will remain an obstacle to the convergence between law and psychoanalysis unless we understand that the origin of this conception lies in the choice of Roman Canon law as its historical representation. Then, it reviews the notion of society, approaching it as a theatrical construction set by discursive practices, allowing the recovery of genealogical knowledge of the reference and to this end, builds on the knowledge of Roman law. Hand-in-hand with a psychoanalytic approach, it points out how a vast social system of interpretations places the law within the transmission of the Interdiction for the subject, transmission which introduces him to the institutional dimension of the limit. We also approach the unconscious aspects of the representation of the subject, by putting a transsexualism case law under the light of its notion of symbolic determinism. Finally, it reflects on the power of the State to divide words and things, that is, the Third separator, category necessary for the operation of law. Consequently, this paper allows law to be seen as refering to the order of life and also calls upon psychoanalysis to deepen the institutional dimension.